2018
DOI: 10.4149/neo_2018_170329n227
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy with bleomycin and cisplatin enhances cytotoxicity in primary and metastatic uveal melanoma cell lines in vitro

Abstract: Electrochemotherapy (ECT) enhances responsiveness to cytotoxic drugs in numerous cell lines in vitro. Clinically ECT is widely applied for skin tumor ablation and has shown efficacy in treating non-resectable colorectal liver metastases. There is limited experience of ECT for ocular tumor therapy. We investigated the cytotoxic effect of bleomycin and cisplatin in combination with electroporation on chemoresistant human uveal melanoma (UM) cell lines in vitro. Four UM cell lines (Mel 270, 92-1, OMM-1, OMM-2.5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
(35 reference statements)
0
16
0
1
Order By: Relevance
“…The reasons for difference in response are multifaceted and include physical features pertinent to electrochemotherapy, such as unavailability of the drug and insufficient coverage with electric field and biological, pertinent to patient, such as previous treatments, difference in tumor microenvironment, mutational status, and so on. 2,14,18 Thus, electrochemotherapy is still evaluated in different types of cancer, either in vitro or in vivo, including colon carcinoma CT26 (in vitro) 19 ; bladder cancer SW780 (in vitro and in vivo) 20 ; fibroblasts, human umbilical vein endothelial cells (HUVEC; in vitro) and two squamous cell carcinomas, CAL-27 and SCC-4 (in vitro) 21 ; ovarian cell lines OvBH-1 and SKOV-3 (in vitro) 22 ; human neuroblastoma SH-SY5Y cells (in vitro) 23 ; BRAF-mutated melanoma cells (SK-MEL-28) and their counterpart without mutation, CHL-1 cells (in vitro) 24 ; chemoresistant uveal melanoma cells (Mel 270, 92-1, OMM-1, OMM-2) (in vitro) 25 ; primary cells from metastatic pancreatic tumors (in vitro) 26 ; human papillomavirus (HPV)-positive head and neck squamous cell carcinoma 2A3 (in vitro and in vivo) 27 ; Lewis lung carcinoma and CT 25 colorectal carcinoma (in vivo) 28 ; conjunctival melanoma CRMM1 and CRMM2 and normal conjunctival epithelial cells HCjE-Gi (in vitro) 29 ; radioresistant head and neck squamous cell carcinoma Fa-DuRR (in vitro and in vivo) 30 ; and small cell lung cancer H69AR cells (in vitro). 31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for difference in response are multifaceted and include physical features pertinent to electrochemotherapy, such as unavailability of the drug and insufficient coverage with electric field and biological, pertinent to patient, such as previous treatments, difference in tumor microenvironment, mutational status, and so on. 2,14,18 Thus, electrochemotherapy is still evaluated in different types of cancer, either in vitro or in vivo, including colon carcinoma CT26 (in vitro) 19 ; bladder cancer SW780 (in vitro and in vivo) 20 ; fibroblasts, human umbilical vein endothelial cells (HUVEC; in vitro) and two squamous cell carcinomas, CAL-27 and SCC-4 (in vitro) 21 ; ovarian cell lines OvBH-1 and SKOV-3 (in vitro) 22 ; human neuroblastoma SH-SY5Y cells (in vitro) 23 ; BRAF-mutated melanoma cells (SK-MEL-28) and their counterpart without mutation, CHL-1 cells (in vitro) 24 ; chemoresistant uveal melanoma cells (Mel 270, 92-1, OMM-1, OMM-2) (in vitro) 25 ; primary cells from metastatic pancreatic tumors (in vitro) 26 ; human papillomavirus (HPV)-positive head and neck squamous cell carcinoma 2A3 (in vitro and in vivo) 27 ; Lewis lung carcinoma and CT 25 colorectal carcinoma (in vivo) 28 ; conjunctival melanoma CRMM1 and CRMM2 and normal conjunctival epithelial cells HCjE-Gi (in vitro) 29 ; radioresistant head and neck squamous cell carcinoma Fa-DuRR (in vitro and in vivo) 30 ; and small cell lung cancer H69AR cells (in vitro). 31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
“…27 For electrochemotherapy with bleomycin, it was demonstrated that it is more effective in melanoma cells that harbor BRAF mutation 24 and in melanoma cells that are chemoresistant. 25 In addition, electrochemotherapy with bleomycin is more effective in radioresistant head and neck tumors than electrochemotherapy with cisplatin, 30 and it is also effective against small cell lung cancer cells. 31 Recently, it was shown that pancreatic tumor cells died from necroptosis rather than from necrosis or apoptosis after electrochemotherapy with bleomycin, cisplatin, and oxaliplatin.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
“…At the same time, the pulse parameters represent only half of the electrochemotherapy treatment components, while the other half depends on the chemotherapeutic drug. Currently, bleomycin and cisplatin are dominating the field [ 9 , 27 , 28 , 29 ], while other approaches using doxorubicin [ 29 , 30 ], vinorelbine [ 13 ] or even paclitaxel [ 16 ] are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…The drawbacks of its application are localized pain, muscle contraction, erythema and edema [ 14 ]. The effect of ECT in ocular melanomas remains unclear, since the research and acquired knowledge in this field is very limited [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%